Cuantificación de la biomasa acumulada en las plantaciones forestales de la provincia de Misiones con potencial para la generación de energía = Quantification of accumulated biomass in forest plantations in the province of Misiones with potential for power generation - Martiarena, Rodolfo (2019)
The aim of this work is to quantify the forest plantations biomass with potential for energy generation in each department of the province of Misiones. Based on the WISDOM methodology (Woodfuels Integrated Supply/Demand Overview Mapping) was obtained the annual biomass increment. The results showed that the greatest increase in biomass accumulation is observed in the northern departments of the province and the highest contribution is made by high density tree plantations without conventional forest management. forest plantation biomass supply, , subtropical region